2018
DOI: 10.1007/s12185-018-2421-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutational subtypes of JAK2 and CALR correlate with different clinical features in Japanese patients with myeloproliferative neoplasms

Abstract: The majority of patients with Philadelphia chromosome-negative myeloproliferative neoplasms (MPNs) harbor JAK2, CALR, or MPL mutations. We compared clinical manifestations of different subtypes of JAK2 and CALR mutations in Japanese patients with MPNs. Within our cohort, we diagnosed 166 patients as polycythemia vera (PV), 212 patients as essential thrombocythemia (ET), 23 patients as pre-primary myelofibrosis (PMF), 65 patients as overt PMF, and 27 patients as secondary myelofibrosis following the 2016 WHO cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
4
14
0
2
Order By: Relevance
“…The findings of increased WBC count, neutrophil rate, and Hb level in the JAK2 ‐ET group in our cohort, compared with the CALR ‐ET group, are consistent with previously reported findings . In addition, the lack of a significant difference in platelet count between the two groups might be due to the small sample size of our cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of increased WBC count, neutrophil rate, and Hb level in the JAK2 ‐ET group in our cohort, compared with the CALR ‐ET group, are consistent with previously reported findings . In addition, the lack of a significant difference in platelet count between the two groups might be due to the small sample size of our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of increased WBC count, neutrophil rate, and Hb level in the JAK2-ET group in our cohort, compared with the CALR-ET group, are consistent with previously reported findings. 30,31 In addition, the lack of a significant difference in platelet count between the two groups might be due to the small sample size of our cohort. There was no significant difference in the median daily dose F I G U R E 2 Median platelet count before and after treatment in each of the three groups.…”
Section: Discussionmentioning
confidence: 88%
“…Using ASO-PCR and conventional Sanger sequencing method, we found that 84.8% of 395 ET patients carried JAK2V617F, CALR, or MPL mutations, underscoring the importance of combined genetic tests for diagnosis of ET patients. The JAK2V617F was the most frequent mutation (56.2%), followed by CALR mutation (27.6%), which is consistent with Chinese (Lin et al, 2015), Japanese (Misawa et al, 2018), Argentinean (Ojeda et al, 2018), and American (Tefferi et al, 2014) ET populations. However, the frequency of CALR exon 9 mutations in our study is higher than that of Thai (Limsuwanachot et al, 2017), Korean (Kim et al, 2015) , Italian (Rotunno et al, 2014) , Polish (Wojtaszewska et al, 2015) , and Brazilian (Nunes et al, 2015) ET patients; in those populations the mutation rate of CALR exon 9 mutations ranged from 12.5% to 15.5%.…”
Section: Discussionsupporting
confidence: 73%
“…Nồng độ LDH tăng cao dẫn đến tăng nồng độ lactat trong máu và tổn thương mô. Chỉ số LDH tăng liên quan đến mức độ nặng của bệnh đã được chỉ ra trong một nghiên cứu gần đây trên bệnh nhân THCVC (Misawa et al, 2018). Ngoài ra, các chỉ số hóa sinh khác như ure, glucose, ferritin, AST và ALT cũng có một số bệnh nhân có các chỉ số này cao hơn bình thường.…”
Section: Chỉ Số Xét Nghiệm Sinh Hóa Máu Bệnh Nhân Thcvcunclassified